Proapoptotic and Antimigratory Effects of Pseudevernia furfuracea and Platismatia glauca on Colon Cancer Cell Lines - Šeklić, Dragana S; Obradović, Ana D; Stanković, Milan S; Živanović, Marko N; Mitrović, Tatjana Lj; Stamenković, Slaviša M; Marković, Snežana D (Food technology and biotechnology, 2018)
The aim of this study is to investigate cytotoxic, proapoptotic, antimigratory and pro-antioxidant effects of methanol, acetone and ethyl acetate extracts of lichens and on colorectal cancer (HCT-116 and SW-480) cell lines. We compared the cytotoxic effects on colorectal cancer cells with the effects obtained from normal human fibroblast (MRC-5) cell line. Tetrazolium (MTT) test evaluated the cytotoxic effects, Transwell assay evaluated cell migration, acridine orange/ethidium bromide (AO/EB) fluorescent method followed the apoptosis, while prooxidant/antioxidant effects were determined spectrophotometrically through concentration of redox parameters. The tested extracts showed considerable cytotoxic effect on cancer cells with no observable cytotoxic effect on normal cells. Ethyl acetate and acetone extract of induced the highest cytotoxicity (IC =(21.2±1.3) µg/mL on HCT-116, and IC =(51.3±0.8) µg/mL on SW-480 cells, respectively, after 72 h), with noteworthy apoptotic and prooxidant effects, and antimigratory potential of methanol extract. extracts induced cytotoxic effects on HCT-116 cells after 72 h (IC <40 μg/mL), while only methanol and acetone extracts had cytotoxic effects on SW-480 cells after 24 h, with proapoptotic/necrotic activity, as a consequence of induced oxidative stress. In conclusion, lichen extracts changed to a great extent cell viability and migratory potential of colorectal cancer cell lines. HCT-116 cells were more sensitive to treatments, had better proapoptotic and antimigratory effects, and both investigated lichen species might be a source of substances with anticancer activity.